Urology at a Glance - Merseburger, Axel S.; Kuczyk, Markus A.; Moul, Judd W. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Urology at a Glance is a concise, practical guide to diagnostic and therapeutic decision making. The book is divided into two parts. The first focuses on the pathway from symptom to diagnosis and covers the full range of symptoms commonly encountered by the urologist. Any particular symptom can be located within a matter of seconds, and in each case differential diagnosis is explained with the aid of a flow chart. The second part of the book is devoted to the pathway from diagnosis to therapy, with each short chapter devoted to a specific diagnosis. Basic information is provided on the disease in question, along with an outline of state of the art treatment options and possible complications. Again, flow charts are used to help the reader to reach the correct therapeutic decision in different circumstances. Numerous high-definition photographs and illustrations, many of them in color, are also included. The editors and authors are leading urological surgeons and oncologists and internationally recognized authorities in their fields. This book will be a great asset in every urologist's office and will also prove invaluable for practitioners in related disciplines.